Discourse Genres in the Digital Age - Delia Andreea OPREA (ACROSS)
Brands, the most luxurious as well as the lesser known, have now fully included the podcast in their storytelling strategy. In October 2018, a communication campaign by LVMH testifies to the emergence of a new form of audio advertising, the podcast, which can be seen as collaborative storytelling or a radio for everyone rather than a radio for all seems to respond to the habits of young people, each year more numerous to listen to these sound programs. With its less conventional, more intimate tone, the podcast has the assets to satisfy a connected and mobile lifestyle. This new media, therefore, gathers a young audience, which proves, moreover, particularly attentive, as indicated by a study published by Médiamétrie in April 2018: more than 80% of downloaded podcasts are listened to and, moreover, in full for the majority (58%). So, the podcast appears as a new intimate and engaged media of luxury houses (and not only). We will therefore identify the podcast series of the various luxury houses, and in a qualitative approach, we will try to observe the characteristics of the podcasts, as a kind of digital discourse.